A qualitative study of blended learning in a Malaysian tertiary institution - Ong, Victor; Cheng, Sheila; Cho, Cho Wei (2009)
This paper attempts to address the question, " What components of a blended learning approach are more appropriate and in what context". The authors examined a set of qualitative data (perception of blended learning, attitude towards technology effectiveness and efficiency of blended learning) through a spider-web model with data drawn from cohorts of Business students currently engaged in blended learning.